2020
DOI: 10.36478/rjnasci.2020.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical Traits and Structural Indices of Malle Cattle Reared in the South Omo Zone of Southwest Ethiopia

Abstract: The study was conducted to morphometrically and morphologically characterized Malle cattle using some predefined qualitative and quantitative parameters and to develop some structural indices to access their type and function. Data were collected through field observations and linear measurements of sample cattle. A total of 360 cattle of different ages of were selected randomly from different locations and morphometrical measurements were carried out on it. Qualitative traits were evaluated using non parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
7

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 16 publications
4
11
7
Order By: Relevance
“…The average value of chest width obtained in this study is lower than those reported by Demerew et al [14] for Malle cows but higher than those reported by Worku [16] for Sheka cows. Further study indicated that Arsi cows have lower chest depth than Fogera cows [18] .…”
Section: Structural Traitscontrasting
confidence: 84%
See 4 more Smart Citations
“…The average value of chest width obtained in this study is lower than those reported by Demerew et al [14] for Malle cows but higher than those reported by Worku [16] for Sheka cows. Further study indicated that Arsi cows have lower chest depth than Fogera cows [18] .…”
Section: Structural Traitscontrasting
confidence: 84%
“…The average height at rump of Arsi cows was shorter than findings of Dereje [15] for Horro cows. The observed value of height at rump was taller than Malle cows that reported from South Omo of Ethiopia [14] .…”
Section: Structural Traitscontrasting
confidence: 58%
See 3 more Smart Citations